2015
DOI: 10.1016/j.nano.2015.07.013
|View full text |Cite
|
Sign up to set email alerts
|

3D tumor tissue analogs and their orthotopic implants for understanding tumor-targeting of microenvironment-responsive nanosized chemotherapy and radiation

Abstract: An appropriate representation of the tumor microenvironment in tumor models can have a pronounced impact on directing combinatorial treatment strategies and cancer nanotherapeutics. The present study develops a novel 3D co-culture spheroid model (3D TNBC) incorporating tumor cells, enodothelial cells and fibroblasts as color-coded murine tumor tissue analogs (TTA) to better represent the tumor milieu of triple negative breast cancer in vitro. Implantation of TTA orthotopically in nude mice, resulted in enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 56 publications
1
42
0
Order By: Relevance
“…We have demonstrated the usefulness of the 3D TNBC model in in vivo setting by implantation of the TTA in the mammary fat pad of nude mice [24, 25]. This preclinical tumor model incorporates aspects of the tumor microenvironment and the neovascular architecture, critical for evaluating nanoparticles and stroma-directed molecular targeting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have demonstrated the usefulness of the 3D TNBC model in in vivo setting by implantation of the TTA in the mammary fat pad of nude mice [24, 25]. This preclinical tumor model incorporates aspects of the tumor microenvironment and the neovascular architecture, critical for evaluating nanoparticles and stroma-directed molecular targeting.…”
Section: Resultsmentioning
confidence: 99%
“…Studies, including our own, have demonstrated the potential of galectin-1 as a therapeutic target by identifying the overexpression of galectin-1 in various human cancers and enrichment in tumor stroma [23, 24]. In addition, we have reported a further induction of galectin-1 expression in tumor stroma as a response to radiation therapy, suggesting that targeting galectin-1 may synergize with radiation therapy [2325]. A number of novel compounds and approaches to block galectin-1 or its activity are currently being evaluated [23].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, we established a tumor cell spheroid model for evaluating the penetration of Cur-NPs into tumor tissue in vitro. 29 In this experiment, curcumin is not suitable for observing drug penetration into compact cell spherical entities because of its weak fluorescence. Therefore, coumarin was used as an indicator instead of curcumin in these experiments.…”
Section: In Vitro Cellular Penetration Of Nps To C6 Spheroidsmentioning
confidence: 99%
“…Various non-tumorigenic cell lines have been grown as hollow acini, including those originating from the breast [12], kidney [13], lung [14], pancreas [15] or prostate [16]. Such 3D cultures have also been used to examine changes in both the growth and morphology of non-tumorigenic cells in altered microenvironments [17,18], to delineate the oncogenetic mechanisms of mutated cells [19,20] and to test the response of tumour cells to various treatments [21,22].…”
Section: Introductionmentioning
confidence: 99%